2020
DOI: 10.1002/capr.12385
|View full text |Cite
|
Sign up to set email alerts
|

Researching online counselling and psychotherapy: The past, the present and the future

Abstract: Using technology as a therapeutic tool is by no means new. During the 1960s, Weizenbaum and his colleagues created a computer programme (ELIZA-which is freely available online for those curious to try it out) that used language rules based upon client-centred counselling principles (Weizenbaum, 1966). Despite the programme's rudimentary nature, Weizenbaum found that participants in his studies engaged in a surprisingly rich way with it. Such interest in the interface between therapy and technology, although no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 21 publications
0
40
0
3
Order By: Relevance
“…The author previously doubted online therapy because she believes that session setting, eye contact, and action are as vital in therapy for therapists and clients to develop a relationship. Terry had a similar thought as me [1] . Then he spoke with a young individual, who informed him that if it wasn't for the online treatment, he wouldn't discuss about his life.…”
Section: Online Therapymentioning
confidence: 76%
See 1 more Smart Citation
“…The author previously doubted online therapy because she believes that session setting, eye contact, and action are as vital in therapy for therapists and clients to develop a relationship. Terry had a similar thought as me [1] . Then he spoke with a young individual, who informed him that if it wasn't for the online treatment, he wouldn't discuss about his life.…”
Section: Online Therapymentioning
confidence: 76%
“…But through the idea changing in some therapists, more therapists start to consider online therapy more positive. Through the process, online therapy would develop more intact and better [1] . When the technology is developed enough at a point, the limitation of online therapy might be eliminated.…”
Section: Online Therapymentioning
confidence: 99%
“…The online counselling and psychotherapy prevalence traced from the early 1960s to the current technological advances in the field (Hanley, 2020) has highlighted some changes towards online practices and service provision. Over the last 30 years, mental health professionals and academics have explored and experimented (both at practice and research-based level) with delivering mental health interventions through the cyberspace (Amichai-Hamburger et al, 2014;Andersson, 2018).…”
Section: The Origins Of Online Counsellingmentioning
confidence: 99%
“…Despite the increasing use of online therapy, variations in demographic characteristics have been observed in the accessing and the utilisation of the online counselling and therapy in comparison to the face-toface counselling (Yeung, Wong & Law, 2001;DuBois, 2004;Hanley, 2012;Novotney, 2017;Hanley, Prescott & Gomez, 2019, Hanley, 2020. Specifically, when gender was considered in relation to the access of the online counselling and therapy services for psychosocial problems, Yeung et al (2001) and Lifeline Ipswich and West Moreton (LIWM, 2001) reported almost as many males as females in their study.…”
Section: Access To Online Counselling and Therapy By Different Demographicsmentioning
confidence: 99%
“…The COVID-19 pandemic has had an immeasurable impact on global health and wellbeing. The consequences have affected mental health while official and selfimposed restrictions have made it difficult for many to access counseling support in rapidly changing circumstances (Hanley, 2020;Costa et al, 2021). College students face unique risks in this respect; many now confront all the common challenges of the pandemic while having to learn remotely, far from traditional campus services.…”
Section: Introductionmentioning
confidence: 99%